Periwayat Syiah dalam Ṣaḥīḥ al-Bukhārī - Husein, Alwi (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2021)
The article reviews the existance of Shi’ite ḥadīth narrator with various levels, in which their report narrated in Sunni authoritative ḥadīth literature namely Ṣaḥīḥ al-Bukhārī. It attempts to examine the chain of transmission (sanad) in Ṣaḥīḥ al-Bukhārī with various classical and contemporary rijāl al-ḥadīth books, such as Ibn Abī Ḥātim (d. 327), Ibn Ḥibbān (d. 354), Yūsuf al-Mizzī (d. 742), al-Dhahabī (d. 748), Ibn Ḥajar (d. 852), al-Suyūṭī (d. 911), Muḥammad Nāṣir al-Dīn al-Albānī (d. 1420) and Shu’ayb al-Arna’ūṭ (d. 1438), to identify the Shia narrators reported in Ṣaḥīḥ al-Bukhārī. By using historical approach and hadīth narrators (rijāl al-Ḥadīth) analysis, the article finds thirty-two Shia narrators, and twenty-four Rāfiḍah narrators composed in Ṣaḥīḥ al-Bukhārī. That is because in methodological perspective, al-Bukhārī does not put beliefs and theological affiliations of the hadīth narrators as parameters for accepting or rejecting the hadīth.